Tipos de familia y desarrollo del lenguaje en niños del nivel inicial II de la escuela “Rosa Josefina Burneo de Burneo” periodo 2024. - Lizalde Agila, Vanessa Carolina (2024)
The present research work of curricular integration dominated Family Types and Language Development to children at the initial level II “Rosa Josefina Burneo de Burneo” School of period 2024. The general objective was: Analyze how the type of family influences in the development of the language in the children at the initial level II. The specific objectives were: Identify the type of family in the initial level II to children of the “Rosa Josefina Burneo de Burneo” school. To describe the language development of the initial level II children of the “Rosa Josefina Burneo de Burneo” school. To determine how the type of family influences the development of language in Initial Level II of the “Rosa Josefina Burneo de Burneo” School. The research used an inductive method, managing a qualitative descriptive approach with a quasi-experimental and cross-sectional design. Likewise, two instruments were developed, an interview with five questions directed at the teachers and the observation sheet directed at the children, to collect information about the type of family and the children language development. The results revealed a diversity in family structures, where the most of children belong to nuclear families, while a minority has other types of family organization. Regarding, language development, was observed that the most of student’s present fluid linguistic progress, with skills to narrate anecdotes and build a coherent phrase. However, we identify a small group of children with difficulties in this aspect, which suggests the need to implement support and stimulation strategies. Furthermore, the data collected to indicate a possible correlation between the type of family and the level of language development in children at this educational level. This information highlights to consider importance characteristics family in the planning and execution of pedagogical activities, with the objective to promotive inclusive and equitable linguistic development. To conclude the research, a proposal was developed to address the issue, which was based on an Activity Guide focused on family types and language development. The implementation of these activities, using a playful methodology, facilitates progress in the children's language area, evidencing an improvement in their communication skills. Keywords: Family types, Language development, Initial education, educational inclusion.